Using the Shoulder Return to Sport After Injury scale to measure psychological readiness before return to play in athletes with traumatic shoulder dislocations: A critically appraised topic - Arnett, H.; Moore, K.; Winkelmann, Z.; Miller, H.; Fraley, A. L. (International Journal of Athletic Therapy & Training, 2025)
The clinical question examined the use of the Shoulder Return to Sport after Injury (SI-RSI) scale to measure athletes` mental readiness after a shoulder injury to improve the return-to-play (RTP) decision-making process. In September 2023, a computerized search of PubMed for evidence was completed. Four articles met the inclusion and exclusion criteria. Outcomes included quantitative evidence of SI-RSI scores and if the athletes RTP. All four studies were evaluated using the Strengthening the Reporting of Observational Studies in Epidemiology Critical Appraisal Checklist. Points were removed for no explanation of statistical analysis, bias, funding, and loss of participants. Two of the included studies concluded that patients who RTP passed the SI-RSI benchmark 73.1% and 81.4% of the time. One study found that 74% of athletes that passed their determined benchmark returned to the same level of play after the injury. One study revealed that participants who RTP scored higher on the reinjury fear and risk subscale compared with those who did not (42.2 ± 23 vs. 27.3 ± 16, p = .02). The Strength of Recommendation Taxonomy checklist concluded a Level C recommendation because of the consistent Levels 2 and 3 evidence across all four studies. This recommendation accounts for the disease-oriented outcomes measured across all studies. This evidence suggests that the SI-RSI helps evaluate psychological readiness before RTP after a shoulder dislocation. Clinically, this may limit the recurrence of shoulder dislocations by requiring athletes to pass the SI-RSI benchmark.